2023
DOI: 10.1111/gbb.12856
|View full text |Cite
|
Sign up to set email alerts
|

The collaborative study on the genetics of alcoholism: Genetics

Abstract: This review describes the genetic approaches and results from the family‐based Collaborative Study on the Genetics of Alcoholism (COGA). COGA was designed during the linkage era to identify genes affecting the risk for alcohol use disorder (AUD) and related problems, and was among the first AUD‐focused studies to subsequently adopt a genome‐wide association (GWAS) approach. COGA's family‐based structure, multimodal assessment with gold‐standard clinical and neurophysiological data, and the availability of pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 221 publications
0
12
0
1
Order By: Relevance
“…Alcohol consumption produces widespread societal problems. Progress is being made to identify its causation and treatment, including genetic interactions [ 4 , 5 ]. Animal models help us understand alcohol’s effects on the brain, and zebrafish have been used to great effect in Robert Gerlai’s laboratory.…”
Section: Neural Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption produces widespread societal problems. Progress is being made to identify its causation and treatment, including genetic interactions [ 4 , 5 ]. Animal models help us understand alcohol’s effects on the brain, and zebrafish have been used to great effect in Robert Gerlai’s laboratory.…”
Section: Neural Systemsmentioning
confidence: 99%
“…Zebrafish are versatile for producing animal models for various conditions, including tumor progression [ 7 ]. Sara Rezzola and colleagues developed a zebrafish platform to evaluate drug efficacy on human and mouse uveal melanoma cells [ 5 ]. They transplanted uveal melanoma tumor xenografts into the zebrafish eye near the developing choroid vasculature.…”
Section: Tumor Biologymentioning
confidence: 99%
“…The Collaborative Study on the Genetics of Alcoholism (COGA) is an ongoing multi-site, family-based study designed to identify genes and traits associated with AUD (total N∼17 762; Dick et al, 2023;Edenberg, 2002;Johnson et al, 2023;Reich et al, 1998). The COGA Prospective (COGA-P) Study (n = 3715) is a longitudinal sub-study of adolescent and young adult offspring with at least one parent who participated in the original COGA study and provided permission for offspring participation (Bucholz et al, 2017).…”
Section: Samplementioning
confidence: 99%
“…Until recent years, heritability studies of stress-related disorders and their phenotypes focused exclusively on genomic inheritance described by classical Mendelian genetics, wherein the DNA sequence carried by germ cell alleles for individual genes confers phenotypes observed in the progeny ( Hayden and Nichols, 1983 ; Clé et al, 1997 ; Day and Bonduriansky, 2011 ). Genome-wide association studies have identified many genetic variations associated with stress-related disorders, ( Purves et al, 2019 ; Coleman et al, 2020 ; Malan-Mü et al, 2014 ; Morimoto et al, 2020 ; Lewis et al, 2010 ; Stoychev et al, 2021 ) including AUD, ( Stoychev et al, 2021 ; Johnson et al, 2023 ; Deak et al, 2022 ; Zhou et al, 2022 ) but these variations only account for a small fraction of heritability, leaving a substantial amount of missing heritability or unexplained variance ( Malan-Mü et al, 2014 ; Morimoto et al, 2020 ; Trerotola et al, 2015 ; Manolio et al, 2009 ; Nadeau, 2009 ; Eichler et al, 2010 ). Consequently, research on stress-related disorder inheritance has increasingly delved into nongenomic inheritance, which considers transmission of environment-induced, epigenetic effects on gene expression that do not alter the underlying DNA sequence ( Bird, 2007 ).…”
Section: Introductionmentioning
confidence: 99%